Evidence-based management of chronic wounds - Jones, Katherine R; Fennie, Kristopher; Lenihan, Amber (Advances in skin & wound care, 2007)
Identify the consistency of current chronic wound care practices with evidence-based recommendations for wound management. A retrospective study based on 400 subject records (venous ulcers, 183; diabetic ulcers, 103; and pressure ulcers, 114). Study records were located at hospitals, wound care centers and clinics, home health agencies, and nursing homes in 4 diverse geographic locations. Chronic wound assessment and evidence-based treatment practices were identified by extensive review of the literature, professional Web sites, and the Agency for Healthcare Research and Quality National Guideline Clearinghouse. Actual delivery of wound care practices was obtained from retrospective chart reviews and a structured data abstraction protocol. Collected data were then compared with recommended practices for consistency, adherence variations, and wound healing across data collection sites. Significant variations occurred in adherence to evidence-based recommendations across sites of care delivery, with selection and application of appropriate dressings showing the greatest need for improvement. Current chronic wound care practices are inconsistent with evidence-based recommendations for wound management. Further studies are needed to determine the best method for translating this information to multiple settings.